(untitled) (Iraqi Journal of Medical Sciences, 2021)
Surgery training continues to be challenging and competitive. Training programs developed multiple strategies to select the best candidates. Applicants continue to improve their chances to join the highly ranked programs. Various skills and strategies have been adopted to optimize their application process. However, many applicants are still in need to prepare for the application process and identify the best strategy to present themselves. In this editorial, we provide practical points to consider when planning to apply and join a surgery training program. Keywords: Surgical training, Application strategies, Surgery programs, Residency application Citation: Tuma FL. Points of consideration in applying to surgery training programs. Iraqi JMS. 2021; 19(2): 134-136. doi: 10.22578/IJMS.19.2.1